The biomechanics of concussion for ice hockey head impact events - Post, A.; Hoshizaki, T. B.; Karton, C.; Clark, J. M.; Dawson, L.; Cournoyer, J.; Taylor, K.; Oeur, R. A.; Gilchrist, M. D.; Cusimano, M. D. (Computer Methods in Biomechanics and Biomedical Engineering, 2019)
The purpose of this research was to conduct reconstructions of concussive and non-concussive impacts in ice hockey to determine the biomechanics and thresholds of concussive injury in ice hockey. Videos of concussive and non-concussive impacts in an elite professional ice hockey league in North America were reconstructed using physical and finite element model methods. Eighty concussive and 45 non-concussive events were studied. Logistic regressions indicate significant thresholds for concussion for linear/rotational acceleration and CSDM10%. Impacts in ice hockey were mostly long duration events, longer than 15 ms. These results have significant implications for helmet standards and development to prevent concussion.